The Impact of Mobile Banking Services on Customer Satisfaction in the Digital Era at PT. Bank Sumut Syariah KCP Hamparan Perak - Rahman, Raudatu Jannah; Miko, Jeroh; Rizki, Bagus (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to examine the impact of mobile banking services on customer satisfaction in the context of digitalization at PT. KCP Hamparan Perak Bank Sumut Syariah. Along with the rapid development of digital technology in the banking sector, mobile banking has become an essential service to improve efficiency, convenience, and overall customer experience. This study employs an associative quantitative research approach to analyze the relationship between mobile banking service quality and customer satisfaction. Primary data were collected through the distribution of structured questionnaires to respondents who actively use mobile banking services. The research population consisted of 1,200 customers of PT. KCP Hamparan Perak Bank Sumut Syariah. Using a purposive sampling technique and the Slovin formula, a sample of 100 respondents was obtained. The collected data were analyzed using multiple linear regression to determine the influence of various mobile banking service dimensions on customer satisfaction. The findings indicate that mobile banking services have a positive and significant effect on customer satisfaction. Among the examined dimensions, information accuracy emerged as the most statistically significant factor affecting customer satisfaction, with a p-value of 0.017. This result highlights the importance of providing accurate, reliable, and timely information through mobile banking platforms. Other factors, including service confirmation, call center access, data confidentiality, and application display, also contribute positively to customer satisfaction, although their effects are relatively less significant. Overall, this study concludes that enhancing mobile banking service quality can strengthen customer trust.